2020
DOI: 10.1080/17434440.2020.1792287
|View full text |Cite
|
Sign up to set email alerts
|

Emerging technologies for diagnostics and drug delivery in the fight against COVID-19 and other pandemics

Abstract: Introduction: A pandemic is the worst-case scenario in the field of infectious diseases. Innovative technologies have the potential to address the challenges associated with the manufacture of personalized drug delivery systems, biosensors, and medical devices during a pandemic. 3D-Printing, microfluidics, and Microelectromechanical systems (MEMS) can provide an important part on this fight, as are cheap, easy to be operated, capable to provide rapid detection and monitoring of a disease, and deliver medicines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…This disruption was palpable for COVID-19 diagnostic tests both in the manufacturing disruption observed and in the downstream logistics infrastructure delivering diagnostic tests to the end users. The tight interoperability of the supply chain as well as the initial (physical and economic) lockdown of China, representing a low-tier supply base for a large part of the manufacturing operations globally, meant that manufacturing would be one of the hardest-hit economic sectors 78 , 79 . Therefore, a dual bottleneck emerged early on in the pandemic in terms of sourcing the biological materials as well as sourcing the primary sources for manufacturing.…”
Section: Mass Production Of Testsmentioning
confidence: 99%
“…This disruption was palpable for COVID-19 diagnostic tests both in the manufacturing disruption observed and in the downstream logistics infrastructure delivering diagnostic tests to the end users. The tight interoperability of the supply chain as well as the initial (physical and economic) lockdown of China, representing a low-tier supply base for a large part of the manufacturing operations globally, meant that manufacturing would be one of the hardest-hit economic sectors 78 , 79 . Therefore, a dual bottleneck emerged early on in the pandemic in terms of sourcing the biological materials as well as sourcing the primary sources for manufacturing.…”
Section: Mass Production Of Testsmentioning
confidence: 99%
“…This literature review identified six articles (TABLE 1), of which two studies [4,5] were reviews about the importance of emerging technology in coping with the pandemic. Another study [6] conducted a search on online sources and went deeper into technically analyzing the role of 3D printing in the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…Lamprou [5] explores bioprinting, a more advanced solution for the use of 3D printing in the field of health, capable of treating specific diseases with a more personalized approach. Through the predictive, preventive and personalized approach (3P), using printing methods adjusted to the requirements of medical products for consumption, it is possible to take the technology of production of medicines into hospitals, accelerating the entire logistics chain associated with the supply of these medicines and allowing researchers, who also need to act on the front of the fight, to adjust doses and carry out their tests with greater speed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As LOC devices can be miniaturized and easily automated, they are an excellent platform for POC diagnostics, and this is already being realized in the literature [ 4 6 ]. Innovations such as 3D printing have the potential to revolutionize LOC technologies and increase accessibility [ 7 ].…”
mentioning
confidence: 99%